2022
DOI: 10.3389/fneur.2022.793253
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in the Treatment of Neurological Diseases

Abstract: Transcranial Magnetic Stimulation (TMS) has widespread use in research and clinical application. For psychiatric applications, such as depression or OCD, repetitive TMS protocols (rTMS) are an established and globally applied treatment option. While promising, rTMS is not yet as common in treating neurological diseases, except for neurorehabilitation after (motor) stroke and neuropathic pain treatment. This may soon change. New clinical studies testing the potential of rTMS in various other neurological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 166 publications
0
41
0
5
Order By: Relevance
“…For the treatment of cerebral dysfunction brought on by a variety of disorders, TMS has shown to be an effective, painless, and non-invasive method of activating or modulating cortical targets in the central nervous system (CNS) ( 29 , 30 ). Motor weakness, aphasia, and dysphagia have all been shown to improve with TMS treatment in clinical studies for individuals recovering from a stroke ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of cerebral dysfunction brought on by a variety of disorders, TMS has shown to be an effective, painless, and non-invasive method of activating or modulating cortical targets in the central nervous system (CNS) ( 29 , 30 ). Motor weakness, aphasia, and dysphagia have all been shown to improve with TMS treatment in clinical studies for individuals recovering from a stroke ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the robust and promising rationale for TMS use for treating neuropsychiatric illnesses, it can be unpleasant, which is the most prevalent adverse effect. Indeed, outcomes may not be as successful as anticipated [13]. Previous studies have similarly revealed this, stating that a lack of success is only observed in some neurologic and psychiatric conditions [9].…”
Section: Shortcomings Of Tmsmentioning
confidence: 91%
“…However, they contend that TMS may be associated with certain risks and safety issues. Finally, Somaa et al found that TMS can be used in pioneering neuropsychiatric diseases such as consciousness disorders, multiple sclerosis, epilepsy, Alzheimer's disease/mild cognitive impairment, and movement disorders[13].search Clinical evidence shows that rTMS could be a viable therapeutic option for neurologic illnesses, namely consciousness disorders, multiple sclerosis, epilepsy, Alzheimer's disease, and movement conditions.…”
mentioning
confidence: 99%
“…In recent years, significant attention has been paid to repetitive transcranial magnetic stimulation (rTMS), a noninvasive and painless technique that has produced many inspiring beneficial results in the research of neurological diseases, such as stroke, Parkinson's disease, and Alzheimer's disease [7,8]. Some published studies have also shown the potential therapeutic effects of rTMS in therapeutic interventions for DOC [9,10].…”
Section: Introductionmentioning
confidence: 99%